Sustainable dietary weight loss intervention and its effects on cardiometabolic parameters and greenhouse gas emissions: study protocol of a randomised controlled trial with overweight and obese adults in Ouagadougou, Burkina Faso. Issue 4 (4th April 2023) - Herrmann, Alina; Gonnet, Anais; Millogo, Roche Modeste; d'Arc Kabré, Wendmintiri Jeanne; Beremwidougou, Tenin Rosine; Coulibaly, Issa; Ouili, Idrissa; Zoromé, Souleymane; Weil, Konstantin; Fuelbert, Hannah; Soura, Abdramane; Danquah, Ina
Abstract : Introduction: The global obesity epidemic and its adverse health effects have reached sub-Saharan Africa. In some urban settings, like Burkina Faso's capital Ouagadougou, up to 43% of the adult population are overweight or obese. At the same time, modernised food systems are responsible for 26% of global greenhouse gas emissions, 50% of land use and 70% of freshwater use. International guidelines on the treatment of overweight and obesity recommend dietary intervention programmes that promote reduced calorie intake and increased physical activity. So far, weight loss interventions rarely consider sustainable dietary concepts, including healthfulness, affordability, cultural appropriateness and environmental friendliness. Therefore, we present a study protocol of a novel randomised controlled trial that aims to establish the effects of a sustainable weight loss intervention on cardiometabolic and environmental outcomes in urban Burkina Faso. Methods and analysis: We conduct a non-blinded randomised controlled trial, comparing a 6-month sustainable diet weight loss intervention programme (n=125) with a standard weight loss information material and 5 min oral counselling at baseline (n=125). Primary outcome is a reduction in fasting plasma glucose of ≥0.1 mmol/L. Outcome measures are assessed at baseline, after 6 months and after 12 months. Ethics and dissemination: Ethical approval for the study has been obtained from the Medical Faculty of Heidelberg University (S-376/2019) and from the Ministry of Health and the Ministry of Higher Education, Scientific Research and Innovation in Ouagadougou, Burkina Faso (No 2021-01-001). The results of the study will be disseminated to local stakeholders at a final project meeting and to the wider research community through peer-reviewed publications and conferences. Trial registration number: DRKS00025991.